Novel practices and trends in grid and cloud computing - Chelliah, Pethuru Raj ca. 20./21. Jahrhundert; Koteeswaran, S. (IGI Global, 2019)
"This book examines the latest trends and transitions in the cloud landscape and explores the role of product vendors, research labs, academic institutions, independent software vendors, IT service organizations, and consulting companies in making the cloud more visible, viable and venerable across different industries"--